2018
DOI: 10.1016/j.jiph.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Human leptospirosis cases in Palermo Italy. The role of rodents and climate

Abstract: Many regions of the world are increasingly exposed to leptospirosis due to poverty, global warming and high urban density. Here, we report a molecular survey for pathogenic Leptospira spp. in rodents and two symptomatic human cases of leptospirosis in the city of Palermo, Italy. Four rodent species were captured in six areas of the city, and a molecular analysis for pathogenic Leptospira spp. on DNA from the kidney samples showed a different prevalence of leptospirosis in all the species of rodents. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
2
21
2
2
Order By: Relevance
“…In a European context, studies that screened at least 10 individuals of one species, generally reported similar prevalence for striped field mice (12.0–19.6%) [ 4 , 16 , 31 ], common voles (14.0–30.0%) [ 4 , 16 , 31 33 ] and field voles (12.0–30.1%) [ 4 , 31 ]. For the yellow-necked mouse only a study in Serbia detected a higher average prevalence with 34.3% [ 33 ], for the wood mouse studies detected similar average prevalence with 15.4% and 18.0% [ 31 , 34 ] and for bank voles our study is in line with a previously published prevalence [ 4 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a European context, studies that screened at least 10 individuals of one species, generally reported similar prevalence for striped field mice (12.0–19.6%) [ 4 , 16 , 31 ], common voles (14.0–30.0%) [ 4 , 16 , 31 33 ] and field voles (12.0–30.1%) [ 4 , 31 ]. For the yellow-necked mouse only a study in Serbia detected a higher average prevalence with 34.3% [ 33 ], for the wood mouse studies detected similar average prevalence with 15.4% and 18.0% [ 31 , 34 ] and for bank voles our study is in line with a previously published prevalence [ 4 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…More generally, the incidence of human cases of leptospirosis is rising in Europe (European Centre for Disease Prevention and Control 2018) as well as the rate of (peri-) urban transmission (Dupouey et al 2014). The increase of the leptospirosis burden in European countries is most likely exacerbated by climate change (global warming and increased frequency and severity of extreme weather events) (Lau 2010), human population growth (Lau 2010), increasing urbanisation (Minter et al 2018), increasing expansion of urban rodents (Boey et al 2019;Dupouey et al 2014;Vitale et al 2018) and other wildlife reservoirs (Baldi et al 2019;Jansen et al 2007), and rise in international travels (Pijnacker et al 2017). Rat population control through culling appears inefficient for reducing the risk of Leptospira transmission to humans (Lee et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Leptospira kirschneri infection seems to be prevalent in testicles and epididymides, while Leptospira interrogans is present in female genital organs. Based on the serovars more often detected in Italy by cultural examination or serology [46][47][48][49][50][51][52], and the rare seropositivity for other serovars [53][54][55], it is likely that the detected L. kirschneri belonged to the serogroup Grippotyphosa. In this study, L. kirschneri infection was only observed in testicles and epididymides, and this could hypothesize this genomospecies as more often associated with the male reproductive system.…”
Section: Discussionmentioning
confidence: 99%